Perbedaan Efektifitas Latihan Wall Pass dan Short Pass Pada Pembelajaran Pendidikan Jasmani SMP Negeri 1 Suwono - Fariz Nugroho; Pandu Krenapati; Osa Maliki (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
The research is motivated by soccer learning which needs to be improved with wallpass and short pass exercises. The problem faced is how to determine the right model of passing practice for students. This can be seen from the two techniques proposed, namely the game and the wall pass and short pass. Both techniques are assumed to be able to improve the accuracy of passing through various previous research results. The purpose of this study is to provide information about exercises that can be applied in learning football. This type of research is experimental research using a quasi-experimental research design. The experiment was carried out in grades 7 and 8, with each sample of 25 students. The data collection technique with observations was carried out using a questionnaire and carried out objectively by the observer. The data analysis technique used in this research is a test technique. Hypothesis testing is done utilizing descriptive analysis of the average difference test. These results indicate that the group that was treated using the Wall-Pass (WP) method had a significant difference from the class that was treated using the Short-Pass (SP) method. Teachers can innovatively develop teaching tools for other passing methods to improve student learning activities. Students need to help each other if they experience problems in implementing the model, and the teacher must be able to ensure that each student in the group can achieve the goal or complete the assigned task.